Broad-Range tunable optical wavelength converter for next generation optical superchannels (2015)
A broad-range tunable all optical wavelength conversion scheme that is based on a dual driven Mach-Zehnder modulator with an integrated microwave generator to tune the channel spacing along the entire C band, is proposed. Successful signal demodulation up to 8 wavelength conversions, in steps of 50-400 GHz of 100 Gbps Nyquist QPSK channels with configurable channel spacing is reported. The proposed wavelength conversion scheme enables flexible wavelength routing on gridless optical networks, as can be seen in the Superchannels with a BER lower than 10-13.